Core Competency Of Soft Skill Towards Project Team Member - Kim, Poh Lan (2020)
Competitive market nowadays increases the complexity of the project. Therefore demanding of competitive team is increase. Besides technical knowledge as a hard skill, soft skills also play an important role to build an effective team to increase project success (Hills, 2018). Numerous research has been done on the understanding of soft skills but there is lack of research to the current performance in Malaysia’s construction team. The purpose of this research conducted is to explore and examine the core soft skills in Klang Valley and Selangor’s construction industry. The objective to be assessed in this research are as: to determine the core soft skills; to evaluate the current performance on soft skills and identify an effective way to improve soft skills for future preparation. The research instrument adopted in this research is quantitative with 5 points Likert scale. There is a total of 156 respondents from 3 different nature of business (developer, consultant, and contractor) which 7 various designations and across generation Y, X and baby boomers. From the collected data, it can be found that all the 16 identified soft skills are important towards project success. Soft skills such as communication, teamwork/engagement and coordination are the 3 most important factors for project success from the finding. Therefore the assessment of current performance is crucial to evaluate the strength and weakness of the team member. Whereas there is the competence gap between core soft skills and current performance. Diminishing or eliminate the competence gap is able to achieve via proper and appropriate improvement strategy which is the 3rd objective in this research. The finding tells that the soft skills able to improve or establish with appropriate strategies. However, there are no single approaches able to overcome all 16 identified soft skills in this research. In a nutshell, the purpose of this research is to provide a better understanding of the core soft skills and performance of the current team member. This is important to explore the appropriate and effective improvement strategies to minimise the competence gap in order to sustain in the competitive construction industry.